Characterization of a high-resolution supercritical differential mobility analyzer at reduced flow rates. Issue 11 (2nd November 2018) - Cai, Runlong; Attoui, Michel; Jiang, Jingkun; Korhonen, Frans; Hao, Jiming; Petäjä, Tuukka; Kangasluoma, Juha
Abstract: Classifying sub-3 nm particles effectively with relatively high penetration efficiencies and sizing resolutions is important for atmospheric new particle formation studies. A high-resolution supercritical differential mobility analyzer (half-mini DMA) was recently improved to classify aerosols at a sheath flow rate less than 100 L/min. In this study, we characterized the transfer functions, the penetration efficiencies, and the sizing resolution of the new half-mini DMA at the aerosol flow rate of 2.5–10 L/min and the sheath flow rate of 25–250 L/min using tetra-alkyl ammonium ions and tungsten oxide particles. The transfer functions of the new half-mini DMA at an aerosol flow rate lower than 5 L/min and a sheath flow rate lower than 150 L/min agree well with predictions using a theoretical diffusing transfer function. The penetration efficiencies can be approximated using an empirical formula. When classifying 1.48 nm molecular ions at an aerosol-to-sheath flow ratio of 5/50 L/min, the penetration efficiency, the sizing resolution, and the multiplicative broadening factor of the new half-mini DMA are 0.18, 6.8, and 1.11, respectively. Compared to other sub-3 nm DMAs applied in atmospheric measurements (e.g. the mini-cyDMA, the TSI DMA 3086, the TSI nanoDMA 3085, and the Grimm S-DMA), the new half-mini DMA characterized in this study is able to classify particles at higher aerosol and sheath flow rates, leading to a higher sizing resolution at the same aerosol-to-sheath flow ratio. Accordingly, the new half-mini DMA can reduce the uncertainties in atmospheric new particle formation measurement if coupled with an aerosol detector that could work at the corresponding high aerosol flow rate. © 2018 American Association for Aerosol Research